Comparison of cross pinning versus lateral three pins in type three supracondylar fracture of distal humerus in children. - Sapkota, Krishna; Wahegaonkar, Krishna; Ranjeet, Niraj; Thapa, Pabin; Thapa, Upendra Jung; Onta, Pratyenta Raj (Asian Journal of Medical Sciences, 2019)
Background: Supracondylar fracture of distal humerus is the most common paediatric fracture. Type III supracondylar fractures should be treated with anatomical reduction and stable Kirschner wire (K- wire, pin) fixation to prevent the cosmetic deformity. The configuration of wires is debatable. Although two crossed K-wires are bio-mechanically stable, there is a risk of iatrogenic ulnar nerve injury. Lateral 3 K-wires is a good alternative. This study was done to compare the outcome of cross K- wire and lateral 3 K-wires in terms of stability. Materials and Methods: This is a prospective study done in Manipal Teaching Hospital. All the Gartland type 3 supracondylar fractures of the distal humerus were treated with closed reduction and stabilized with K wires. In Group I, fractures were stabilized with cross K wire fixation and in group II they were stabilized with 3 lateral K-wires. The patients were followed up at 4-5 weeks for wire removal and at 3 months and 6 months after surgery. Baumann's angle, a functional outcome as per Flynn's criteria, and range of motion were recorded in each visit. Outcomes were compared in term of displacement of fracture. Result: Seventeen children in each group were taken up for the study. There were no significant differences in term of patients and fracture character. No patients had significant loss of reduction at final follow up. There is no statistically significant difference seen in mean changes of Bauman's angle. According to Flynn's criteria good result was seen in more than 95% of cases in both groups. Conclusion: Both cross K-wires and Lateral 3 K-wires provide good stability. Fixation of supracondylar fracture from lateral side had an advantage of no risk of iatrogenic Ulnar nerve injury. Addition of third K-wire from lateral side provides good stability as that of cross K- wire fixation.